Implementation of Inclusive Finance in Empowering Micro, Small and Medium Enterprises (UMKM) at Micro Waqf Banks - Rahma Jaziyatul Chikmiyah (EKONOMIKA SYARIAH : Journal of Economic Studies, 2021)
This study aimed to analyze the impact of the implementation of financial inclusion at Al-Fithrah Micro Waqf Bank regarding the empowerment of Empowering Micro, Small and Medium Enterprises (MSME). Even though MSME sectors have become a central foundation for the economy, the capital limitation is still considered a classic problem. It influences the government to release National Strategy Financial Inclusion to provide financial services that all levels of society can access. The indicators inclusive financial consists of access, usage and quality to realize empowerment through financing and assistance. This research used a descriptive qualitative method, and data were collected through interviews, observations, and documentation. The results showed that the financial inclusion component had been implemented but still has many potentials to be maximized. The components of access and usage have been appropriately implemented in terms of physical aspects and prices that are easily accessible to customers. These two components have an impact on increasing customer Islamic financial literacy. In the quality component, product variations are expected to fulfill the different business needs of customers. Meanwhile, financing has not significantly impacted fulfilling the welfare component’s capital needs  because the nominal value is too small. Furthermore, business assistance has a more significant impact on improving the business and spiritual aspects of clients. Penelitian ini bertujuan untuk menganalisis dampak penerapan keuangan inklusif pada Bank Wakaf Mikro Al-Fithrah terhadap pemberdayaan UMKM di sekitarnya. Meskipun sektor UMKM telah menjadi fondasi yang cukup sentral bagi perekonomian, keterbatasan permodalan masih menjadi masalah klasik UMKM. Hal ini mendorong pemerintah untuk mengeluarkan Strategi Nasional Keuangan Inklusif yang bertujuan untuk memberikan layanan keuangan yang dapat diakses seluruh lapisan masyarakat. Indikator keuangan inklusif yang terdiri dari akses, penggunaan dan kualitas diterapkan untuk mewujudkan pemberdayaan UMKM melalui pembiayaan dan pendampingan. Penelitian ini menggunakan metode deskriptif kualitatif melalui pengumpulan data wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa komponen keuangan inklusif telah diimplementasikan namun masih berpotensi untuk dimaksimalkan. Komponen akses dan penggunaan sudah terlaksana dengan baik dilihat dari segi fisik dan harga yang mudah dijangkau nasabah. Kedua komponen tersebut berdampak pada peningkatan literasi keuangan syariah nasabah. Pada komponen kualitas, variasi produk diharapkan dapat memenuhi kebutuhan modal nasabah yang berbeda. Sedangkan untuk komponen kesejahteraan, pembiayaan belum memberikan pengaruh signifikan untuk memenuhi kebutuhan permodalan karena nilai nominal yang terlalu kecil. Selain itu, program pendampingan usaha (HALMI) memiliki dampak yang lebih signifikan terhadap peningkatan usaha dan spiritual pelanggan.